(untitled) (Zien Journal of Social Sciences and Humanities, 2025)
Theodore Dreiser’s An American Tragedy (1925) exposes the myth of the American Dream by revealing its gendered limitations. Through the protagonist Clyde Griffiths and the women in his life—Roberta Alden and Sondra Finchley—Dreiser illustrates how class and gender restrict social mobility. While Clyde, as a man, can exploit relationships for advancement, women face insurmountable societal penalties, particularly regarding sexuality and economic agency. Dreiser’s naturalist approach underscores how systemic forces, rather than individual merit, determine fate. This paper argues that the novel critiques the American Dream as an unequal construct, offering enduring insights into gender and class disparities in American society.